Waiting for the night song - Dalton, Julie Carrick (Forge, 2021)
"An urgent message from her long-estranged best friend Daniela brings Cadie back to her childhood home. There, they are forced to face a dark secret that ended both their idyllic childhood bond and the magical summer that takes up more space in Cadie's memory than all her other years combined."--Publisher's description.